Note-Taking Technique Achievement In Narrative Text At Senior High School - Dimas Priagung Banar Syahputra; Arin Inayah (Buana Pendidikan, 2022)
The researcher researched note-taking techniques in teaching reading comprehension of English subjects. This research would like to know how students’ note-taking technique ability results are in narrative text. The research does in senior high school. This research does during three months by using 22 populations. The research design is qualitative research. The research instrument is a test. Based on the results of this study, the researcher concludes that the use of note-taking techniques has an influence on the ease of students or writers in writing and compiling summaries. The results of using note-taking techniques in writing also affect the ease of readers to understand the contents of the entire text from the summary made by students or writers. However, the results of this study also show deficiencies in the discussion to find out about the differences in students' thinking models in understanding sentences and students' writing creativity so that there are differences in the quality of students' writing. So, researchers can accept and give suggestions to future researchers to conduct similar and more complex research.